Assessing metacognitive online reading strategy usage among EFL teachers in Indonesia - Rianto, Agus (Penerbit Universiti Kebangsaan Malaysia, 2022)
A significant amount of research on Metacognitive Online Reading Strategies (MORS) is currently focused on EFL/ESL students, and only a few studies have examined the participation of EFL teachers. This quantitative study, therefore, aimed at assessing the use of these strategies among EFL teachers in Indonesia. Analyses of the strategy usage was based on factors of gender, teaching status, and internet literacy levels. Via a Google form application, a MORS survey was employed as the data collection instrument. The gathered data were analyzed descriptively and inferentially using t-tests, Pearson correlation, and linear regression. The results showed that in reading online academic materials, the teachers used support strategies more frequently than problem-solving strategies and global strategies. Overall, the teachers employed these strategies at a moderate to high level. Based on gender and internet literacy, significant differences in the overall and strategy category uses were discovered. There were significant correlations between the teachers’ internet literacy levels and their use of the overallstrategies, the support strategies, and the global strategies, but no correlation between the internet literacy levels and the problem-solving strategies. The internet literacy levels were found to be strong predictors of the overall and category strategy uses. The findings of this research offer a wide variety of educational implications for EFL reading.